1996
DOI: 10.1080/03610739608254016
|View full text |Cite
|
Sign up to set email alerts
|

Intrusions in alzheimer's disease in immediate and delayed memory as a function of presentation modality

Abstract: Young and elderly participants, and participants with Alzheimer's disease (AD) were compared via the suffix paradigm, where a not-to-be-recalled item is appended onto sequences to be immediately recalled. This task was followed by delayed tasks. In immediate recall, AD subjects showed both extralist and suffix intrusions. Recall of auditorily as compared with visually presented stimuli was superior, with the difference increasing in older subjects. The auditory but not the visual suffix produced an end-of-sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The fact that the DMS48– group was impaired when compared with the DMS48+ group on the number of intrusions performed during free recall may be suggestive of AD, as this feature has been reported to be a hallmark of this disease (Manning, Greenhut-Wertz, & Mackell, 1996; Fuld, Katzman, Davies, & Terry, 1982). Efficiency of cueing was also found to be lower, as already found in a previous study, and suggestive of a genuine memory impairment related to medial temporal dysfunction rather than an apparent memory dysfunction related to frontal dysfunction (Barbeau et al, 2004).…”
Section: Discussionmentioning
confidence: 92%
“…The fact that the DMS48– group was impaired when compared with the DMS48+ group on the number of intrusions performed during free recall may be suggestive of AD, as this feature has been reported to be a hallmark of this disease (Manning, Greenhut-Wertz, & Mackell, 1996; Fuld, Katzman, Davies, & Terry, 1982). Efficiency of cueing was also found to be lower, as already found in a previous study, and suggestive of a genuine memory impairment related to medial temporal dysfunction rather than an apparent memory dysfunction related to frontal dysfunction (Barbeau et al, 2004).…”
Section: Discussionmentioning
confidence: 92%
“…It is known, for instance, that older adults tend to commit more intrusions in episodic recall than do young adults (Balota et al, 1999; Kahana, Howard, Zaromb, & Wingfield, 2002; Zacks, Radvansky, & Hasher, 1996). Furthermore, both intrusion rates and types of intrusions committed may have diagnostic value for clinical dementias and in particular for Alzheimer's disease (Davis, Price, Kaplan, & Libon, 2002; Fuld, Katzman, Davies, & Terry, 1982; Manning, Greenhut-Wertz, & Mackell, 1996; Watson, Balota, & Sergent-Marshall, 2001).…”
mentioning
confidence: 99%
“…These intrusions may reflect an inability to inhibit irrelevant or inappropriate memories from entering consciousness. Correspondingly, several studies reported specific deficits in tasks that have been suggested to involve cognitive inhibition mechanisms, for example, the Stroop task (Spieler, Balota, & Faust, 1996), negative priming (Vaughan et al ., 2006) or directed forgetting (Manning, Greenhut‐Wertz, & Mackell, 1996). Furthermore, inhibitory deficits in individuals with DAT may lead to impaired performance on word recall (Fuld, Katzman, Davies, & Terry, 1982) and sentence comprehension (Faust, Balota, Duchek, Gernsbacher, & Smith, 1997).…”
Section: Introductionmentioning
confidence: 99%